Apertura y Cierre de Empresas Turísticas del cantón Colta, provincia de Chimborazo - Freire Montesdeoca, Cynthia Lizbeth (2024)
ABSTRACT: The objective of the research was to analyze the influence of factors in the tourism environment on the opening and closing of tourist companies in the Colta canton, using a mixed research methodology. Surveys and semi-structured questionnaires were employed to collect quantitative and qualitative data on the personal factors of tourism entrepreneurs, tourism environment factors, and planning factors of government institutions related to tourism and tourist satisfaction. The results indicated that the personal factors of the entrepreneur have a significant impact on business dynamics, emphasizing the need to develop entrepreneurial and management skills. The positive influence of the tourism environment on the business sector was confirmed, highlighting the importance of policies that promote a favorable environment for tourism development. Although the research did not find statistically significant evidence regarding the influence of planning on the opening and closing of tourist companies, its importance for future research is emphasized. Strengthening the intervention of government agencies in business processes is recommended to ensure the quality and sustainability of the sector. Keywords: Opening, closing, development, entrepreneurs, ventures.